Analisis Potensi Parkir, Studi Kasus Di Kota Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
To analyse the demand of on street parking, a large amount of data is needed. There would be a problem to compile and analysis the data, especially to match the registration number of the parked vehicles. A software program, PARKIR, therefore, has been developed to compile and analyse the data, by using Turbo Pascal version 7.0. This program was used to analyse the potential of on street parking within the city of Yogyakarta. Survey has been carried out in the whole on street parking facilities in the city of Yogyakarta, for the whole days, on the working days, Saturdays and Sundays. Patrol survey method has been employed. Data has been analysed by using PARKIR software program, to calculate the number of parked vehicles, parking accumulation, parking time and parking duration. Further analysis has been carried out to calculate parking index, turn over and to estimate the local government income from parking retribution. It has been analysed also some alternative solutions for parking policy.